Robotic-Assisted Dissection of Bulky Lymph Nodes in Cervical Cancer - Ahmet Göçmen; Fatih Şanlıkan; Muhittin Eftal Avcı (Case Reports in Obstetrics and Gynecology)
The resection of bulky lymph node metastases, which may provide a therapeutic benefit, has been proposed in several studies based on laparotomy and laparoscopy. There is no published study in the literature examining the resection of bulky lymph node metastases using a robotic technique. In this report, we presented a patient with cervical cancer who underwent robotic-assisted dissection of bulky lymph nodes. The robotic-assisted operation time was 255 minutes, and the mean console time was 215 minutes. The estimated blood loss was 70 mL. The number of lymph nodes retrieved was 28, and the number of the dissected paraaortic lymph nodes was 13. The number of the lymph node metastases was eight. The bulky lymph nodes which are difficult to be eradicated with standard radiation therapy can be resected with robotic-assisted surgery and successful resection of the lymph nodes can improve the treatment strategy. This minimal invasive technique is safe and feasible for bulky lymph node dissection.